Peripheral Airway Responsiveness to Sub-maximal Exercise in Asymptomatic Cigarette Smokers. - Pokhrel, B R; Chatopadhyaya, S; Paudel, B H (Kathmandu University Medical Journal, 2012)
Background Cigarette smoking is one of the cardinal causes for the development of bronchial hyperresponsiveness among the smokers. Objectives This study was perspectively designed to determine the peripheral bronchial responsiveness to sub-maximal exercise challenge in the asymptomatic smokers. Methods The subjects were between age of 18-25 years without any findings of cardio-respiratory diseases. We performed the 5 min step test exercise at intensity of 80 to 90% of maximum predicted heart rate in 42 young adult male asymptomatic smokers to examine the effect of cigarette smoking on airway responsiveness. Forced expiratory spirogram was recorded before and at 0, 5, 10, 15 min after the completion of exercise. Pre- to post exercise drop in Forced Expiratory Volume in first second ? 15% was considered hyperresponsive to the challenge. Result The analysis of data (mean± SE) indicated the bronchial hyper-responsiveness in 22 (52%) smokers. The post exercise recovery time pattern showed drop in forced expiratory spirogram from the resting baseline in the responsive smokers and the maximum percentage fall in the parameters or increase in airway resistance which reflect the peripheral airway integrity such as Forced Expiratory Flow 25% (20.30 ±2.18 Vs 7.88 ±3.23, p<0.01), Forced Expiratory Flow 50% (18.46 ±4.40 Vs 1.93 ±2.78, p<0.01), Forced Expiratory Flow 75% (23.94 ±3.68 Vs 0.80 ±4.72, p<0.001) and Forced Expiratory Flow 25-75% (32.50 ±4.79 Vs 3.64 ±3.32, p<0.001) was significantly higher in the responsive than non-responsive subgroup of the smokers. Conclusion The occurrence of peripheral airway resistance is more in the responsive than non-responsive subset of smokers to the exercise challenge and hence more prone to develop obstructive airway disease in the long run. <!–[if !supportEmptyParas]–> <!–[endif]–> DOI: http://dx.doi.org/10.3126/kumj.v9i3.6295 Kathmandu Univ Med J 2011;9(3):159-64